Bilateral Simultaneous Total Knee Arthroplasty May Not Be Safe Even in the Healthiest Patients. (17th February 2021) - Warren, Jared A.; Siddiqi, Ahmed; Krebs, Viktor E.; Molloy, Robert; Higuera, Carlos A.; Piuzzi, Nicolas S.
Abstract : Background: Bilateral total knee arthroplasty (TKA) has been shown to increase both mortality and complications, but has potential benefits including decreased length of stay, rehabilitation time, and costs. The purpose of this study was to use data from a nationally representative database to identify if there is a population of patients undergoing TKA in whom bilateral TKA can be safely performed, by comparing 30-day mortality and complication rates with those of patients undergoing unilateral TKA. Methods: The National Surgical Quality Improvement Program (NSQIP) was queried to compare 30-day rates of mortality and any complication between bilateral TKA and unilateral TKA. A total of 8, 291 patients who underwent bilateral TKA were matched 1:1 with a unilateral TKA control cohort (n = 315, 219) by morbidity probability, which is a cumulative variable encompassing demographic characteristics, comorbidities, and laboratory values. Patients were divided into quartiles based on morbidity probability. Binary logistic regression comparing bilateral TKA and unilateral TKA for the same quartiles was performed to establish if any population could safely have bilateral TKA performed. Results: Bilateral TKA had an increased risk for all complications (p < 0.001) and major complications (p < 0.001) when compared with unilateral TKA regardless of health status. For all complications, there was a greater than threefold increase for the first quartile (healthiest patients) (p < 0.001), a greater than fourfold increase for the second and third quartiles (p < 0.001), and a greater than threefold increase for the fourth quartile (least healthy patients) (p < 0.001). For major complications, there was a greater than twofold increase for the first quartile (p = 0.001) and the second quartile (p < 0.001), an almost threefold increase for the third quartile (p < 0.001), and a 57% increase for the fourth quartile (p = 0.005). Conclusions: This study will assist shared decision-making between orthopaedic surgeons and patients by suggesting that bilateral TKA may not be as safe an option for even healthy individuals compared with unilateral TKA. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.